Investigação do tratamento com N-acetilcisteína nos comportamentos relacionados à ansiedade durante a síndrome de abstinência do etanol e na resposta cardiovascular induzida pelo estresse em ratos - Casula, Lígia Cury (Universidade Federal de São Carlos, 2019)
N-acetylcysteine (NAC) for decades, has been shown to have beneficial effects for the treatment of some diseases. Recently, based on central glutamatergic neurotransmission, psychiatric disorders and the stress response have been explored.Ethanol addiction and cardiovascular and autonomic changes in the exposure of stress are considered public health problems and responsible for a large number of deaths in the world.Both problems are related to dysfunctions in central glutamatergic neurotransmission. Thus, our first objective was to investigate whether NAC was able to reverse one of the negative emotional states of the ethanol withdrawal syndrome, anxiety. For this, Wistar rats were induced to anxiety-related behaviors in the Elevated Plus Maze (EPM) after withdrawing the treatment of ethanol offered in their drinking fountains and intraperitoneal injections of ethanol (2 g / kg) for 11 days. During ethanol exposure, the animals also received 10-day intraperitoneal injections of NAC at doses of 30; 60 and 120 mg / kg and on day 11, on the day of the EPM test, the animals did not draw NAC or only received a single injection of NAC 2 hours before the EPM test. Ethanol concentrations in blood were also checked to analyze ethanol pharmacokinetic changes and the best time to investigate withdrawal symptoms. The second objective of the study investigated the effects of NAC on the possible reversal of cardiovascular parameters altered by exposure of the stress of repeated or acute restriction. The results showed that NAC was not able to revert anxiety-related behaviors after treatment withdrawal with ethanol. The NAC also did not reverse the cardiovascular changes induced by restriction stress such as blood pressure, heart rate and tail temperature. However, in the response of the baroreflexs, the NAC presented a potential effect in altering the their sensitivity. Acutely 2 hours before analysis of baroreflex functions, NAC reduced tachycardia. After 24 hours of its acute administration and after its chronic administration, NAC presented bradyadic increase and reduction of intrinsic heart rate in normotensive animals. When associated with stress exposure reduced sympathetic tone, increased intrinsic heart rate and reduced bradycardic function. Therefore, its use requires caution, due to changes in the cardiac requencia and changes in baroreflex sensitivity.
Investigation of N-acetylcysteine ​​treatment in anxiety-like behaviors during ethanol withdrawal syndrome and in cardiovascular stress-induced response in rats
Keywords: N-acetilcisteína; Etanol; Estresse; Ansiedade; Barorreflexo; N-acetylcysteine; Ethanol; Stress; Anxiety; Baroreflex; CIENCIAS BIOLOGICAS; CIENCIAS DA SAUDE::FARMACIA; CIENCIAS DA SAUDE; CIENCIAS BIOLOGICAS::FARMACOLOGIA::FARMACOLOGIA CLINICA; CIENCIAS BIOLOGICAS::FARMACOLOGIA::FARMACOLOGIA GERAL; CIENCIAS BIOLOGICAS::FARMACOLOGIA::NEUROPSICOFARMACOLOGIA; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA DE ORGAOS E SISTEMAS::FISIOLOGIA CARDIOVASCULAR; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA DE ORGAOS E SISTEMAS::NEUROFISIOLOGIA; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA GERAL